Socio-cultural rehabilitation of children with ASD in the State Darwin Museum. Program «Others» - Kubasova T.S (Moscow State University of Psychology and Education, 2017)
The State Darwin Museum has been carrying out work on the socio-cultural rehabilitation of people with disabilities with museum facilities for the many years. The museum is actively developing the direction on the complex adaptation for visitors with autism spectrum disorders.